Co-Delivery System of Curcumin and Colchicine Using Functionalized Mesoporous Silica Nanoparticles Promotes Anticancer and Apoptosis Effects - Khaled AbouAitah; Ahmed A. F. Soliman; Anna Swiderska-Sroda; Amr Nassrallah; Julita Smalc-Koziorowska; Stanislaw Gierlotka; Witold Lojkowski (MDPI AG, 2022)
Purpose: Many natural agents have a high anticancer potential, and their combination may be advantageous for improved anticancer effects. Such agents, however, often are not water soluble and do not efficiently target cancer cells, and the kinetics of their action is poorly controlled. One way to overcome these barriers is to combine natural agents with nanoparticles. Our aim in the current study was to fabricate an anticancer nanoformulation for co-delivery of two natural agents, curcumin (CR) and colchicine (CL), with a core-shell structure. Using cancer cell lines, we compared the anticancer efficacy between the combination and a nanoformulation with CL alone. Methods: For the single-drug nanoformulation, we used phosphonate groups to functionalize mesoporous silica nanoparticles (MSNs) and loaded the MSNs with CL. Additional loading of this nanoformulation with CR achieved the co-delivery format. To create the structure with a core shell, we selected a chitosan-cellulose mixture conjugated with targeting ligands of folic acid for the coating. For evaluating anticancer and apoptosis effects, we assessed changes in important genes and proteins in apoptosis (p53, caspase-3, Bax, Bcl-2) in several cell lines (MCF-7, breast adenocarcinoma; HCT-116, colon carcinoma; HOS, human osteosarcoma; and A-549, non-small cell lung cancer). Results: Nanoformulations were successfully synthesized and contained 10.9 wt.% for the CL single-delivery version and 18.1 wt.% for the CL+CR co-delivery nanoformulation. Anticancer effects depended on treatment, cell line, and concentration. Co-delivery nanoformulations exerted anticancer effects that were significantly superior to those of single delivery or free CL or CR. Anticancer effects by cell line were in the order of HCT-116 > A549 > HOS > MCF-7. The lowest IC50 value was obtained for the nanoformulation consisting of CL and CR coated with a polymeric shell conjugated with FA (equivalent to 4.1 ± 0.05 µg/mL). With dual delivery compared with the free agents, we detected strongly increased p53, caspase-3, and Bax expression, but inhibition of Bcl-2, suggesting promotion of apoptosis. Conclusions: Our findings, although preliminary, indicate that the proposed dual delivery nanoformulation consisting of nanocore: MSNs loaded with CL and CR and coated with a shell of chitosan-cellulose conjugated folic acid exerted strong anticancer and apoptotic effects with potent antitumor activity against HCT-116 colon cells. The effect bested CL alone. Evaluating and confirming the efficacy of co-delivery nanoformulations will require in vivo studies.